Better Migration Management: A good approach to cooperating with countries of origin and transit? - Steffen Angenendt; David Kipp (Stiftung Wissenschaft und Politik (SWP), 2017)
Since the EU and Turkey concluded their refugee agreement, the central Mediterranean is becoming increasingly important again and is currently the most travelled route for irregular immigration to Europe. A proportion of the refugees and migrants on this route in 2016 came from the Horn of Africa and East Africa. As part of the Khartoum Process, the EU is seeking to cooperate with the countries in this region on migration policy. The Better Migration Management (BMM) programme is one part of these en-deavours. Some civil society actors criticize the programme because they believe it dis-regards human rights and validates despotic regimes. Analysis shows that this claim has, so far, been unjustified. Nevertheless, there is a risk that such cooperation may embolden authoritarian leaders who commit human rights violations. It is, therefore, all the more important to pay attention not only to effectiveness, but also to sustaina-bility and legitimacy when establishing partnerships on migration policy.
Keywords: 320